Peran Pembelajaran PAI dalam Membangun Karakter Mahasiswa di STIKES Griya Husada Sumbawa - Ovi Soviya; Lina Eta Safitri (Moral : Jurnal kajian Pendidikan Islam, 2025)
Islamic Religious Education (PAI) plays an important role in shaping the character of students in Indonesia, especially at higher health education institutions such as STIKES Griya Husada Sumbawa. This article aims to explore the role of PAI learning in building student character and identify the challenges faced in its implementation. This research used a qualitative method with a field study approach, involving 30 students from the Nursing, Public Health and Midwifery Study Programs. Data was collected through in-depth interviews, participant observation, and documentation, and analyzed using triangulation to ensure validity. The research results show that the majority of students consider PAI learning to be very important, although there are challenges related to the relevance of the material and teaching methods used. PAI learning is proven to have a positive impact on student character, however the application of these values ​​in everyday life still faces obstacles. These findings emphasize the importance of improvements in the PAI curriculum and teaching methods to increase its effectiveness in forming superior student character and integrity.